2014
DOI: 10.1049/iet-cta.2013.0818
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of hybrid stochastic systems by disordered controllers

Abstract: This study considers the stabilisation problem of hybrid stochastic systems by regular and stochastic state feedback controllers whose operation modes suffer a disordering phenomenon. By introducing an augmented Markov chain, a new operation mode is used to describe such a disagreement. Without designing a controller with new operation mode directly, a kind of controllers only having original operation mode is developed by using the non-fragile control method, whose condition is given as linear matrix inequali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Thus, it is necessary and meaningful to consider this general case. Because of the obtained results with LMI forms here, it is concluded that they could be extended to the above general case, where some existing methods such as [5,10] will be used to deal with this uncertainty.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, it is necessary and meaningful to consider this general case. Because of the obtained results with LMI forms here, it is concluded that they could be extended to the above general case, where some existing methods such as [5,10] will be used to deal with this uncertainty.…”
Section: Resultsmentioning
confidence: 81%
“…As we know, Markovian jump systems (MJSs) are very appropriate to describe dynamical systems experiencing changes in their structures or parameters randomly. Up to now, many important research topics of this kind of system, such as stability analysis [1][2][3][4], stabilization [5][6][7], ∞ control and filtering [8][9][10][11], output control [12,13], state estimation [14,15], adaptive control [16,17], and synchronization [18,19], have been considered. By investigating most results on the stability in the literature, it is seen that the classical Lyapunov stability guaranteeing the stability in an infinite-time interval was usually considered.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some necessarily additional variables and inequalities are introduced to obtain LMI conditions, where the variables are to be computed instead of being given beforehand. Because of the given results with LMI forms, the above general case could be handled by exploiting the methods in this paper and [46,47] together.…”
Section: Remarkmentioning
confidence: 99%
“…Moreover, another case that operation mode is disordering or unmatched [48,49] is included, where S i F = S, but l satisfying λ l (k) = 1 is not equal to mode i satisfying r k = i. Finally, but not the last, when S i F ⊂ S, it is said that controller (3) with ∆ l ≡ I q is named to be a partially mode-available and unmatched controller.…”
Section: Remarkmentioning
confidence: 99%